On Multipliers from Spaces of the Bergman Type to the Hardy Spaces in a Polydisk - Shamoyan, R. F. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We describe coefficient multipliers from spaces of the Bergman type to the Hardy spaces.